Combat surgical workload in Operation Iraqi Freedom and Operation Enduring Freedom: The definitive analysis. Issue 1 (July 2017) - Turner, Caryn A.; Stockinger, Zsolt T.; Gurney, Jennifer M.
Abstract : BACKGROUND: Relatively few publications exist on surgical workload in the deployed military setting. This study analyzes US military combat surgical workload in Iraq and Afghanistan to gain a more thorough understanding of surgical training gaps and personnel requirements. METHODS: A retrospective analysis of the Department of Defense Trauma Registry was performed for all Role 2 (R2) and Role 3 (R3) military treatment facilities from January 2001 to May 2016. International Classification of Diseases, Ninth Revision, Clinical Modification procedure codes were grouped into 18 categories based on functional surgical skill sets. The 189, 167 surgical procedures identified were stratified by role of care, month, and year. Percentiles were calculated for the number of procedures for each skill set. A literature search was performed for publications documenting combat surgical workload during the same period. RESULTS: A total of 23, 548 surgical procedures were performed at R2 facilities, while 165, 619 surgical procedures were performed at R3 facilities. The most common surgical procedures performed overall were soft tissue (37.5%), orthopedic (13.84%), abdominal (13.01%), and vascular (6.53%). The least common surgical procedures performed overall were cardiac (0.23%), peripheral nervous system (0.53%), and spine (0.34%). Mean surgical workload at any point in time clearly underrepresented those units in highly kinetic areas, at times by an order of magnitude or more. The published literature always demonstrated workloads well in excess of the 50th percentile for the relevant time period. CONCLUSIONS: The published literature on combat surgical workload represents the high end of the spectrum of deployed surgical experience. These trends in surgical workload provide vital information that can be used to determine the manpower needs of future conflicts in ever-changing operational tempo environments. Our findings provide surgical types and surgical workload requirements that will be useful in surgical training and placement of medical assets in future conflicts. LEVEL OF EVIDENCE: Epidemiologic study, level III; Care management, level III.